Comparative study of CA19-9 levels as tumor marker in sera and tissues of patients with stomach, colon and rectum cancers - Al-dujaili, Amar H.; Al-Taei, Wafaa F.; Turky, Kisma M; Al-Ubaidi, Gheid H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: CA19-9 is among a group of mucin glycoprotein sialosyl lewis antigen (SLA) having come to be recognized as a circulating cancer associated antigen for gastrointestinal cancer. Basic research into cancer causation will be a powerful determinant of intervention in the transformation process reinforcing the need for developing effective molecular tumor biomarkers for early detection of malignant evolution in tissues of organs i.e. stomach, colon and rectum. In this study, we make a comparsion between the levels of CA19-9 in sera and tissues of patients with these diseases to see if their levels are proportional and if it is a tumor marker that affect with malignant cells in tissues of these organs. Patients and methods: Carbohydrate antigen 19-9 (CA19-9) levels were measured in sera and tissues’ of 8 patients with stomach cancer (G1), 8 patients with colon cancer(G2), 8 patients with rectum cancer (G3) and 30 healthy subjects (G4), by the enzyme-linked immunosorbent assay (ELISA) technique. Results: The results of CA19-9 levels in sera were (42.625±33.088; 47.013±0.318 and 10.938±0.979)U/ml for G1, G2 and G3 respectively compared with serum CA19-9 level of G4, which was 7.74±4.92 U/ml. The results were found to be significantly higher than control group (p < 0.005).The results of CA19-9 levels in tissues’ homogenate were (1170.25±8.45; 535.75±263.46 and 483.75±16.37)U/ml for G1, G2 and G3 respectively. The results revealed significantly higher levels of CA19-9 in tissue’s homogenate of each patients group compared with the serum levels of the same patients (p < 0.005). Conclusions: Normal level of CA19-9 were found in sera of rectum cancer patients compare to the cutoff value 37U/ml in literatures 1,2, but it is significantly higher than our control group. , Significant high levels of CA19-9 were found in sera of colon cancer patients. , Sera of stomach cancer patients showed elevation in CA19-9 level in 50% of cases. , Significant high levels of CA19- 9 were found in tissue’s homogenate of rectum, colon and stomach cancer patients compared to its levels there serum.